Deubiquitinase USP29 Governs MYBBP1A in the Brains of Parkinson’s Disease Patients - Jo, Areum (J Clin Med, 2019)
The inactivation of parkin by mutation or post-translational modification contributes to dopaminergic neuronal death in Parkinson’s disease (PD). The substrates of parkin, FBP1 and AIMP2, are accumulated in the postmortem brains of PD patients, and it was recently suggested that these parkin substrates transcriptionally activate deubiquitinase USP29. Herein, we newly identified 160 kDa myb-binding protein (MYBBP1A) as a novel substrate of USP29. Knockdown of parkin increased the level of AIMP2, leading to ultimately USP29 and MYBBP1A accumulation in SH-SY5Y cells. Notably, MYBBP1A was downregulated in the ventral midbrain (VM) of Aimp2 knockdown mice, whereas the upregulation of MYBBP1A was observed in the VM of inducible AIMP2 transgenic mice, as well as in the substantia nigra of sporadic PD patients. These results suggest that AIMP2 upregulates USP29 and MYBBP1A in the absence of parkin activity, contributing to PD pathogenesis.